EFEKTIFITAS STRATEGI REPUBLIK RAKYAT TIONGKOK DALAM MENGUASAI LAUT CHINA SELATAN PASCA PUTUSAN BADAN ARBITRASE INTERNASIONAL 2016 - Hendy Rizal Muhammad; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains the Chinese strategy ineffectiveness to dominate the South China Sea post Permanent Court Arbitration in 2016. The Court declined the China’s nine dash line claim and decided to accept Philipine’s claim on the region dispute. This research also explores the Chinese strategy to dominate the South China Sea which militarily speaks louder regarding to its massive military power development and its huge number of economic power especially since 1990s.The research applies two approach which are balance of power and maritme security approach. The maritime security approach consists of two aspects: maritme security regime and maritime security community. The maritime security approach is used to explain the South China Sea regional secuity complexity. The strategy theory is used to explain China’s strategy to dominate the South China Sea. This research is developed by qualitative methods with library studies technique.The result of this research shows that South China Sea regional security problem complexity has caused China’s strategy became ineffective. These complexity consists of China’s aggresiveness in the region, the internal and external balance of power in the region, and security dilemma in the South China Sea. These complexity have made China’s strategy became ineffective.Key Words: China, South China Sea, Permanent Court Arbitration, Ineffective Strategy, Security Complexity, Balance of Power, and Security Dilemma.